2018
DOI: 10.3389/fphys.2018.00827
|View full text |Cite
|
Sign up to set email alerts
|

A Bout of High Intensity Interval Training Lengthened Nerve Conduction Latency to the Non-exercised Affected Limb in Chronic Stroke

Abstract: Objective: Evaluate intensity-dependent effects of a single bout of high intensity interval training (HIIT) compared to moderate intensity constant-load exercise (MICE) on corticospinal excitability (CSE) and effects on upper limb performance in chronic stroke.Design: Randomized cross-over trial.Setting: Research laboratory in a tertiary rehabilitation hospital.Participants: Convenience sample of 12 chronic stroke survivors.Outcome measures: Bilateral CSE measures of intracortical inhibition and facilitation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(67 citation statements)
references
References 117 publications
(153 reference statements)
0
64
0
Order By: Relevance
“…When the brain nerve cells are damaged, the body functions controlled by these nerve cells are impaired. Stroke treatment and rehabilitation are usually divided into two stages, namely, acute and chronic phases of stroke [4, 5]. During the acute phase, the patient's corresponding function is restored when the impaired neural connections are recovered within the called sensitive time-limited window.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the brain nerve cells are damaged, the body functions controlled by these nerve cells are impaired. Stroke treatment and rehabilitation are usually divided into two stages, namely, acute and chronic phases of stroke [4, 5]. During the acute phase, the patient's corresponding function is restored when the impaired neural connections are recovered within the called sensitive time-limited window.…”
Section: Introductionmentioning
confidence: 99%
“…In clinics, motor deficits are some of the most prevalent symptoms, and 69% of stroke patients have some degree of motion disability of the upper extremity [12]. Fortunately, clinic investigations in both human and animal models demonstrate that massive and intensive motion training can induce cortical changes and reorganization, which construct a relative ability to produce skilled action [4]. Thus, motor function improvements beyond the subacute stage might be induced by rehabilitative therapies.…”
Section: Introductionmentioning
confidence: 99%
“…This result is somewhat surprising because one might presume that the lesioned hemisphere would be less responsive to changes induced by interventions, especially in the chronic stage of stroke. However, Abraha et al 19 also found exercise-induced changes only in the lesioned hemisphere. Thus, it appears that post-stroke, the lesioned hemisphere may in fact be more predisposed to acute exercise priming than the non-lesioned hemisphere.…”
Section: Discussionmentioning
confidence: 97%
“…In two other studies utilizing high-intensity exercise, one study found that a graded exercise test modulated the ratio of SICI levels between hemispheres but did not change SICI levels within a hemisphere nor did it change MEP amplitudes 18 . The other study utilized high-intensity interval training and found that MEP latencies from the lesioned hemisphere were lengthened after exercise, but intracortical measurements were unaffected 19 . MEP amplitudes were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…SICI was induced using paired-pulse TMS [i.e., conditioning (S1)—test (S2) stimuli delivered at a fixed interstimulus interval (ISI)]. During study parameterization, ISIs were tested (range 2–6 ms, 0.5 ms increments, randomized order) to identify the ISI producing maximal inhibition for each subject and hemisphere (44, 45). In the rest condition S1 was set at stimulator output equal to 80% RMT (23); during active motor tasks S1 was set at 70% AMT (46).…”
Section: Methodsmentioning
confidence: 99%